The Effect of Liquidity, Leverage, Profitability and Firm size on Financial Distress with GCG as a Moderation Variable - Khansa, Lauda; Nugroho, Wawan Sadtyo; Nurcahyono, Nurcahyono (Universitas Muhammadiyah Semarang, 2022)
Financial difficulties will arise due to the company's inability to compete, and when a company's finances are in trouble, these conditions trigger bankruptcy. This study examines the effect of liquidity, leverage, profitability and firm size on financial distress with good corporate governance as a moderation variable. The population of this study is mining companies listed on the Indonesia stock exchange from 2018 to 2021 and using purposive sampling. The data analysis used was moderate regression analysis with the help of the SPSS 24 tool. The results showed that liquidity did not affect financial distress, leverage positively affected financial distress, and profitability and firm size negatively affected financial distress. Good corporate governance weakens the effect of liquidity and profitability on financial distress. Good corporate governance strengthens profitability and financial distress. Good corporate governance does not moderate the relationship between firm size and financial distress.